The Effect of Active Mathematics on the Statistical Literacy Skills of Children Aged 5–6 Years at TK Tri Insani Permata Pekanbaru - Anggraini, Ana Lutfia; Solfiah, Yeni; Kurnia, Rita (Universitas Pahlawan Tuanku Tambusai, 2025)
Early childhood is a golden period of development, making it essential to introduce statistical concepts in an active and meaningful way. However, statistics instruction in kindergartens tends to be passive and misaligned with children's developmental characteristics. This study employed a quantitative approach using a quasi-experimental one-group pretest-posttest design involving children aged 5–6 years at TK Tri Insani Permata Pekanbaru. Observations were conducted before and after treatment without a control group. The average score increased from 35.67% (pretest) to 78.00% (posttest). Prior to treatment, 93.33% of children were in the